The Effects of Using Murdoch Integrated Approach (Mia) Together with the TPACK Model to Enhance Reading Comprehension of the 11th Grade Student - Kunkittikowit, Pannanee; Jantarach, Vachira (Journal of Dhamma for Life, 2025)
The purposes of this research were to 1) compare the achievement of English reading comprehension skills of the grade 11th students before and after using Murdoch Integrated Approach (MIA) together with the TPACK MODEL and 2) study the students’ satisfaction towards learning by using Murdoch Integrated Approach (MIA) together with the TPACK MODEL. The samples of this study consisted of 40 students in the second semester of the 2024 academic year. The samples were selected by cluster sampling, the methodology was the one – group pretest – posttest design. The research instruments were 1) lesson plan on English reading comprehension skills of grade the 11th students using Murdoch Integrated Approach (MIA) together with the TPACK MODEL 2) Pre- test and post-test of reading comprehension using Murdoch Integrated Approach (MIA) together with the TPACK MODEL, and 3) questionnaire to investigate the satisfaction of the grade 11th students towards learning using Murdoch Integrated Approach (MIA) together with the TPACK MODEL. The mean (x̄), standard deviation (S.D.), dependent samples t-test and content analysis were employed to analyze the data. The findings were as follows: 1. The achievement of English reading comprehension skills of the samples after learning using Murdoch Integrated Approach (MIA) together with the TPACK MODEL was higher than that before learning using Murdoch Integrated Approach (MIA) together with the TPACK MODEL at the .05 level.2. The satisfaction of the grade 11th students towards learning using Murdoch Integrated Approach (MIA) together with the TPACK MODEL was high.